Microeconomics for today - Tucker, Irvin B., author (Boston : Cengage, 2019)
The most reader-friendly economics approach available, MICROECONOMICS FOR TODAY, 10E by national award-winning educator Irvin Tucker presents Macro and Micro economic concepts using a writing style that is both engaging and clear, no matter what your current level of economic understanding. A unique presentation and visual learning system, colorful graphs, and Causation Chains clarify and illustrate important economic principles. The book concisely presents and reinforces core concepts, while online resources immediately facilitate assessment of understanding, and will study the latest information on economic growth, income distribution, federal deficits, environmental issues, and other developments in economics today. The book's easy-to-follow format demonstrates how to apply principles to your everyday life, while numerous printed and digital study tools help you further master key current economic principles.
1 - Introducing the economic way of thinking 2 - Production possibilities, opportunity cost, and economic growth 3 - Microeconomics fundamentals 4 - Markets in action 5 - Price elasticity of demand and supply 6 - Consumer choice theory 7 - Production costs 8 - Perfect competition 9 - Monopoly 10 - Monopolistic competition and oligopoly 11 - Labor markets 12 - Income distribution, poverty, and discrimination 13 - Antitrust and regulation 14 - Environmental economics 15 - International trade and finance 16 - Economies in transition 17 - Growth and the less-developed countries
Includes bibliographical references and index.
In English text.
Keywords: Microeconomics